Long-term effects of mepolizumab in patients with severe eosinophilic asthma: a 6-year real-life experience - Stanziola, Anna Agnese; Candia, Claudio; Nazzaro, Gerardo; Caso, Antonio; Merola, Claudia; Gallotti, Lorena; Maniscalco, Mauro (Frontiers in Pharmacology, 2024)
Background. Severe eosinophilic asthma (SEA) is often linked to a dysregulation in the Interleukin-(IL)-5 axis. Mepolizumab, a humanized monoclonal antibody, reduces eosinophils by directly binging to IL-5, potentially restoring homeostatic eosinophil biology, with a significant impact on quality of life, acute exacerbations and oral corticosteroids (OCS) elimination in SEA patients. While its shortand middle-term effects are well described, no study has so far investigated its long-lasting effects in SEA patients. The aim of our study was therefore to explore the effects of a long-term, six-year continuous treatment with mepolizumab on clinical control and clinical remission in a cohort of SEA patients.Methods. We conducted a retrospective review of clinical records of patients who were prescribed mepolizumab between June 2017 and April 2018. We collected demographical, functional, and clinical data from visits performed at baseline and then at the specified timepoints and checked if patients had reached clinical remission after 6 years. We assessed asthma control test (ACT), exacerbation rate, and OCS elimination dose at six years. Clinical Remission (CR) was defined on the basis of the elimination of OCS and the contemporary presence of all the following: (1) stable lung function; (2) no exacerbation in the previous 12 months; (3) acceptable symptom control (ACT ≥ 20).Of 86 patients screened, 62 were included in the final analysis. Our study suggests that mepolizumab is effective and well tolerated after a six-year course of continuous treatment in patients with SEA. We reported a prevalence of 28 (46.8%) patients who reached complete CR at 72 months from the treatment start. 75% of patients eliminated the maintenance OCS already after one year of treatment; this proportion reached the 87% within the sixth year of treatment. Conclusions. Mepolizumab proved to be effective in real-life after 6 years of treatment, inducing a complete clinical remission in the 46.8% of patients, with sustained improvements in quality of life, exacerbation rate, OCS intake and lung function.